Formation in Movement: An Art Exploration - Metcalf, Katy Jayne (Auckland University of Technology, 2020)
Formation in Movement is an active art exploration of the undulating nature of art practice itself. The project emerges through a folding and enfolding of responses to material and encounter while aiming to elude the stagnation that comes from representation. During a process of material play, work evolves intuitively through a series of movements – movements in the materials themselves, in the formation of material ‘objects’, and in the ideas as they surface through the making. In this practice, works are ‘finished’ when they are unfinished; once a work begins to open more questions than it answers, it gains a certain momentum that folds back into future works. This subconscious weaving of questions leads to a non-linear chronology, as the connections between works only become clear in retrospect. The singular constant throughout this practice is change itself.
Keywords: Form; Formation; Movement; Art; Exploration; Material; Sculpture; Studio; Practice; Response; Change; Encounter; Undulating; Subconsious; Momentum; Formless; Process; Emergence; Non-representational; Unfinished; Finished; Research; Enfolding; Question; Non-linear; Objects; Artwork; Digital; Mixed Media; Digital Manipulation